Assessing Vocational Teachers' Performance Using the Rasch Model: Exploring the Impact of Experience, Employment Status, and Certification - Indrayani, Sari; Hariri, Hasan; Riswandi, Riswandi; Handoko, Handoko (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study analyzes factors influencing vocational high school (SMK) teachers' performance using the Rasch Model. It examines the impact of teaching experience, employment status, certification, and educational qualification on four competencies: Learning Planning and Implementation (LPI), Professionalism Development and Learning Media (PDL), Administration and Ethics in Teaching (AET), and Evaluation, Guidance, and Learning Innovation (EGL). A quantitative survey was conducted with 452 vocational teachers in Lampung Province. Data were analyzed using Rasch Model fit statistics, Differential Item Functioning (DIF), and Wright Map analysis to evaluate teacher competency levels and assessment validity. The results show that teaching experience significantly influences performance, with senior teachers excelling in AET and EGL. Civil servant teachers (PNS) demonstrate greater consistency, while honorary teachers show higher adaptability. Certified teachers perform better in structured pedagogy but show less engagement in instructional innovation. Postgraduate teachers (S2) participate more in professional development but exhibit varied teaching approaches. The Wright Map confirms a strong differentiation in competency levels, while DIF analysis highlights the need for targeted training interventions. The study recommends structured mentorship for junior teachers, advanced training for mid-career educators, and leadership programs for senior teachers. It contributes to teacher assessment research by applying Rasch Model-based psychometric analysis in vocational education. Unlike traditional studies, this research integrates Rasch Model and DIF analysis for a more precise evaluation of teacher performance.